GROWTH PERFORMANCE AND SURVIVAL RATE OF SAND LOBSTER (Panulirus homarus sp.) IN AN INDOOR SYSTEM - Khaerudin, Khaerudin; Indrayati, Artin; Aulia, Deni; Sabariyah, Nunung; Umidayati, Umidayati (Aurelia Journal, 2025)
Sand lobster (Panulirus homarus sp.) is one of the promising fishery commodities with high economic value and is considered a leading export species in Indonesia's fisheries sector. The cultivation of sand lobster using floating net cages (KJA) in the sea still faces many challenges. Therefore, innovative cultivation technologies for lobsters are urgently needed. This study aims to assess the growth performance and survival rate of sand lobsters cultivated in a closed system (indoor system). The research was conducted using four fiberglass tanks measuring 4 x 2 x 1 m (water height 0.5 m). The average initial body weight (IBW) of the lobster seed used was 79.8 ± 5.8 (mean ± SE) with a stocking density of 10 individuals/m². The feed provided consisted of trash fish and golden apple snails, with a feeding rate of 15% of the total biomass. Growth sampling was conducted every three weeks. Sand lobsters cultivated for nine weeks (63 days) had an average final body weight (FBW) of 91.1 ± 5.2 grams/individual. The weight gain (WG) and specific growth rate (SGR) of the sand lobsters during the study were 14.2 ± 1.5% and 0.22 ± 0.02%, respectively. The feed conversion ratio (FCR) during the study was 10.1 ± 0.1, while the average daily growth (ADG) was 0.19 ± 0.01 grams/day. The survival rate (SR) of the sand lobsters decreased over the maintenance period, reaching 75.6 ± 2.8% by the end of the study.